PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA KARTU RAHASIA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Wiwik Okta Susilawati; Yulia Darniyanti; Gusti Kumala Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the lack of innovative, interesting, and entertaining media available in schools, as well as the inadequate facilities available in schools, especially in the teaching of Pancasila education. Efforts to overcome these problems require efforts in developing fun learning media, in the form of secret card snake and ladder learning media. This research aims to produce secret card snake and ladder media in the learning of Pancasila Education in grade IV of Elementary School. The type of research is development research, which uses a 4-D development model consisting of the stages of define, design, development, and disseminate. The results obtained from the development of the secret card ladder snake media obtained 83.8% validator results, from Practicality 89.83% and Effectiveness 96.6%